The solidary function of contracts and the protection of the ecologically balanced environment - Santiago, Mariana Ribeiro; Ortega, Ana Clara da Silva (Electronic Journal "Fórum Ambiental da Alta Paulista", 2024)
The aim of this article is to analyze current contractual principles and how they can serve to protect the environment. Initially, it seeks to analyze the figure of the contemporary contract and the consequences of its social function. Next, the concept of the right to an ecologically balanced environment and the necessary search for sustainability are studied. Finally, aspects concerning the solidary function of contracts, which is different from the social function, and solidary liability for damage caused to the environment are analyzed. It emerges that tackling the environmental crisis and the quest for sustainability also involves adopting contracts in line with the solidary function of contracts. The method of approach used in the research is Miguel Reale's three-dimensional legal dialectic, accompanied by the bibliographic research procedure.
Keywords: Contracts; Solidary function; Environment